Direct stimulation of human fibroblasts by nCeO2in vitro is attenuated with an amorphous silica coating. Issue 1 (December 2015) - Davidson, Donna; Derk, Raymond; He, Xiaoqing; Stueckle, Todd; Cohen, Joel; Pirela, Sandra; Demokritou, Philip; Rojanasakul, Yon; Wang, Liying
Abstract Background Nano-scaled cerium oxide (nCeO2 ) is used in a variety of applications, including use as a fuel additive, catalyst, and polishing agent, yet potential adverse health effects associated with nCeO2 exposure remain incompletely understood. Given the increasing utility and demand for engineered nanomaterials (ENMs) such as nCeO2, "safety-by-design" approaches are currently being sought, meaning that the physicochemical properties (e.g., size and surface chemistry) of the ENMs are altered in an effort to maximize functionality while minimizing potential toxicity.In vivo studies have shown in a rat model that inhaled nCeO2 deposited deep in the lung and induced fibrosis. However, little is known about how the physicochemical properties of nCeO2, or the coating of the particles with a material such as amorphous silica (aSiO2 ), may affect the bio-activity of these particles. Thus, we hypothesized that the physicochemical properties of nCeO2 may explain its potential to induce fibrogenesis, and that a nano-thin aSiO2 coating on nCeO2 may counteract that effect. Results Primary normal human lung fibroblasts were treated at occupationally relevant doses with nCeO2 that was either left uncoated or was coated with aSiO2 (amsCeO2 ). Subsequently, fibroblasts were analyzed for known hallmarks of fibrogenesis, including cell proliferation and collagen production, as well as the formation of fibroblastic nodules. The results of this study are consistent with this hypothesis, as we found that nCeO2 directly induced significant production of collagen I and increased cell proliferationin vitro, while amsCeO2 did not. Furthermore, treatment of fibroblasts with nCeO2, but not amsCeO2, significantly induced the formation of fibroblastic nodules, a clear indicator of fibrogenicity. Suchin vitro data is consistent with recentin vivo observations using the same nCeO2 nanoparticles and relevant doses. This effect appeared to be mediated through TGFβ signaling since chemical inhibition of the TGFβ receptor abolished these responses. Conclusions These results indicate that differences in the physicochemical properties of nCeO2 may alter the fibrogenicity of this material, thus highlighting the potential benefits of "safety-by-design" strategies. In addition, this study provides an efficientin vitro method for testing the fibrogenicity of ENMs that strongly correlates within vivo findings.